Multi-tier cropping system to enhance resource utilization, profitablity and sustainablity of Bt cotton (Gossypium hirsutum) production system - SANKARANARAYANAN, K; NALAYINI, P; PRAHARAJ, C S (The Indian Journal of Agricultural Sciences, 2013)
Intercropping of short duration vegetables with cotton, forming a multi-tier system may transform the cost intensive cotton production system to a more remunerative and sustainable one. Thus, to study the appropriate combination of vegetables as an intercrop(s) for multi-tier in cotton, an on station field trial was conducted during fall seasons (August to February) of 2005-06 and 2006-07 under irrigated condition at Central Institute for Cotton Research, Regional Station, Coimbatore. The treatment combinations comprised eight Bt cotton based multi-tier intercropping systems in additive series along with a sole Bt cotton tried in a randomised block design with three replications. Results revealed that crop growth attributes, yield traits and yield of cotton were not significantly influenced by different multi-tier cropping systems. Seed cotton yield in different intercropping systems ranged from 2.55 to 2.91 Mg/ha, whereas sole cotton yield was 2.62 Mg/ha. None of the cotton quality parameters showed any significant differences under multi-tier cropping system. Yet, highest gross return (` 150278/ha) , net return (` 99232/ha), per day profitablity (` 662/day) and seed cotton equivalent yield (7.37 tonnes/ha) were with multi-tier system of cotton + radish + cluster bean+ beet root (T2). This also showed highest relative production efficiency (RPE, 182%), relative economic efficiency (REE, 309 %) and land equivalent ratio (LER, 3.6) amongst the intercropping systems evaluated. Diversity index (DI), measuring the diversity, was also highest (3.8) with the above system (T2) indicating self-sustaining nature of the system.